2020
DOI: 10.1007/s00382-020-05569-9
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric tropical modes are important drivers of Sahelian springtime heatwaves

Abstract: Heatwaves pose a serious threat to human health worldwide but remain poorly documented over Africa. This study uses mainly the ERA5 dataset to investigate their large-scale drivers over the Sahel region during boreal spring, with a focus on the role of tropical modes of variability including the Madden–Julian Oscillation (MJO) and the equatorial Rossby and Kelvin waves. Heatwaves were defined from daily minimum and maximum temperatures using a methodology that retains only intraseasonal scale events of large s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 88 publications
1
17
0
Order By: Relevance
“…These recommendations are in tune with previous work by Guigma et al (2020b), who identified tropical modes of variability as important large-scale drivers of Sahelian heatwaves. Precisely, the activity of the Madden Julian Oscillation (MJO), the equatorial Rossby (ER) and Kelvin (EK) waves in the Equatorial West Africa sector (0-10°N), where convection peaks in spring, significantly modulates the frequency and spatial distribution of heatwaves in the Sahel.…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…These recommendations are in tune with previous work by Guigma et al (2020b), who identified tropical modes of variability as important large-scale drivers of Sahelian heatwaves. Precisely, the activity of the Madden Julian Oscillation (MJO), the equatorial Rossby (ER) and Kelvin (EK) waves in the Equatorial West Africa sector (0-10°N), where convection peaks in spring, significantly modulates the frequency and spatial distribution of heatwaves in the Sahel.…”
Section: Introductionsupporting
confidence: 80%
“…Then, each segment undergoes a wavenumber frequency filtering similarly to (Wheeler and Kiladis 1999), to retain the harmonics of the MJO, ER and EK waves. The exact characteristic wavenumbers, periodicities and equivalent depths used to detect each of these three modes of tropical variability are the same as those used in Guigma et al (2020b), and are shown in Table 1. The outcome of the filtering for each mode and for each segment is a 1506-day long timeseries of filtered OLR data at each of the global tropics grid-cell.…”
Section: Predicted Tropical Mode Activity and Link With Heatwavesmentioning
confidence: 99%
See 3 more Smart Citations